2020
DOI: 10.1021/acsanm.0c02296
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Neutron Scattering Investigation of MgCl2 Nanoparticle-Based Ziegler–Natta Catalysts for Olefin Polymerization

Abstract: The effect of nanosize and structural disorder on the MgCl2 support of Ziegler–Natta catalysts has been investigated in terms of induced changes to their vibrational spectroscopic fingerprint. In particular, the inelastic neutron scattering (INS) technique was used, which allowed sampling of the whole lattice dynamics of the support. The experimental INS spectra of several ball-milled, polycrystalline, samples of MgCl2 were collected for the first time and were compared to simulated spectra from quantum-mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…More recently, different nanostructures were obtained in terms of disorder and morphology, which in turn influence the overall catalytic performance. The investigation was further extended by looking at the lattice dynamics of MgCl 2 systems by means of inelastic neutron scattering (INS) spectroscopy, which is a valuable method to probe the motion of atoms within a material and hence understand the structural disorder of nanosized systems. In recent years, some of the authors have sharpened the use of FT-IR spectroscopy of adsorbed carbon monoxide as a technique to get information on the MgCl 2 exposed surfaces and their relative extent. , The method, which was attempted for the very first time by Zakharov and co-workers, was demonstrated to be particularly powerful, especially when the MgCl 2 surfaces are not fully occupied by the other components and/or by side residues of the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, different nanostructures were obtained in terms of disorder and morphology, which in turn influence the overall catalytic performance. The investigation was further extended by looking at the lattice dynamics of MgCl 2 systems by means of inelastic neutron scattering (INS) spectroscopy, which is a valuable method to probe the motion of atoms within a material and hence understand the structural disorder of nanosized systems. In recent years, some of the authors have sharpened the use of FT-IR spectroscopy of adsorbed carbon monoxide as a technique to get information on the MgCl 2 exposed surfaces and their relative extent. , The method, which was attempted for the very first time by Zakharov and co-workers, was demonstrated to be particularly powerful, especially when the MgCl 2 surfaces are not fully occupied by the other components and/or by side residues of the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…One example is chlorine (total neutron scattering cross section = 16.8 barn) in the MgCl 2 support employed in the Ziegler-Natta catalysts, for which it was possible to detect the effect of the decrease in particles dimension and of the increase of disorder as a function of the ball-milling time. [9] On the other hand, INS is also extremely powerful to investigate the species formed under in situ conditions in the presence of a H-donor, among all H 2 . This is particularly valuable when investigating hydrogenation catalysts, as the methodology provides a unique perspective over the hydrogenous species active for the hydrogenation process.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the last few years it was also demonstrated that the modern instrumental resolution is sufficient to investigate also non‐hydrogenous materials and to focus on other elements with a sufficiently high neutron scattering cross section. One example is chlorine (total neutron scattering cross section=16.8 barn) in the MgCl 2 support employed in the Ziegler‐Natta catalysts, for which it was possible to detect the effect of the decrease in particles dimension and of the increase of disorder as a function of the ball‐milling time [9] . On the other hand, INS is also extremely powerful to investigate the species formed under in situ conditions in the presence of a H‐donor, among all H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, polymer characteristics such as bulk density, melt flow behavior, as well as molecular weight, and comonomer composition distribution (CCD) can significantly influence the performances of polyolefin materials. 6 However, the correlation between Ziegler-Natta catalyst structure and properties of the resulted polymers remains a great challenge. [7][8][9] Recently, the studies into the relationship between HDPE particle size/distribution and its characteristics have attracted a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size distribution (PSD) of the used catalyst determines the products' PSD 4,5 . In addition, polymer characteristics such as bulk density, melt flow behavior, as well as molecular weight, and comonomer composition distribution (CCD) can significantly influence the performances of polyolefin materials 6 . However, the correlation between Ziegler‐Natta catalyst structure and properties of the resulted polymers remains a great challenge 7–9 …”
Section: Introductionmentioning
confidence: 99%